Utilization Of Renewable Energy Resource Pva With Parallel Current Sharing Dc-Dc Booster Converters (International Journal of Engineering and Computer Science, 2015)
In this paper, a new current sharing technique on general case of N paralleled DC–DC boost converters is presented. The proposed optimization is based on the knowledge of individual boost parameters. Every loss through the structure are modeled b equivalent resistors. Using an accurate online estimation of those resistors, the losses through each individual converter can be de termined. Then, a new current sharing scheme is deﬁned aiming to maximize the global efﬁciency of the overall structure. To verify the proposed method, simulations and experiments have been realized on a three-parallel boost converters structure.